Experimental investigation of the aerodynamics of a freight train passing through a tunnel using a moving model. (September 2019) - Iliadis, P; Soper, D; Baker, C; Hemida, H
The objective of this study was to investigate the aerodynamic effects of a freight train passing through a tunnel. The nose entry generates a complex pattern of reflective pressure waves (piston effect) which can lead to intense aerodynamic forces. Previous research on the topic has focused on passenger trains because of higher speeds. The experiments of this study use a 1/25th scaled moving model at the TRAIN Rig at a speed of 33.5 m/s with a blockage ratio of 0.202. The monitored pressure along the tunnel wall can increase up to almost 1000 Pa because of the initial compression wave, while it drops when an expansion wave or the tail passes by. The maximum pressure is observed at the train nose due to air stagnation (1500 Pa) where the flow is steady, while the roof and sides experience negative pressures due to unsteady flow separation. The effect of loading configuration is significant as partially loaded trains can create a second pressure peak on the tunnel walls (after the initial compression wave) and affect the flow at the tunnel entrance wall. Under the current testing conditions, the results indicated compliance with the requirements of the Technical Specification for Interoperability and a constant pressure gradient of the initial compression wave which is in contrast with the passenger train's two-part gradient. Further work on the topic could provide visual information about the exiting jet towards the portal and the separation bubble around the train.